Highly Variable Pharmacokinetics of Tyramine in Humans and Polymorphisms in OCT1, CYP2D6, and MAO-A - Rafehi, Muhammad; Faltraco, Frank; Matthaei, Johannes; Prukop, Thomas; Jensen, Ole; Grytzmann, Aileen; Blome, Felix G.; Berger, Ralf Günter; Krings, Ulrich; Vormfelde, Stefan V.; Tzvetkov, Mladen V.; Brockmöller, Jürgen (Frontiers in Pharmacology, 2019)
Tyramine, formed by the decarboxylation of tyrosine, is a natural constituent of numerous food products. As an indirect sympathomimetic, it can have potentially dangerous hypertensive effects. In vitro data indicated that the pharmacokinetics of tyramine possibly depend on the organic cation transporter OCT1 genotype and on the CYP2D6 genotype. Since tyramine is a prototypic substrate of monoamine oxidase A (MAO-A), genetic polymorphisms in MAO-A may also be relevant. The aims of this study were to identify to what extent the interindividual variation in pharmacokinetics and pharmacodynamics of tyramine is determined by genetic polymorphisms in OCT1, CYP2D6, and MAO-A. Beyond that, we wanted to evaluate tyramine as probe drug for the in vivo activity of MAO-A and OCT1. Therefore, the pharmacokinetics, pharmacodynamics, and pharmacogenetics of tyramine were studied in 88 healthy volunteers after oral administration of a 400 mg dose. We observed a strong interindividual variation in systemic tyramine exposure, with a mean AUC of 3.74 min*µg/ml and a high mean CL/F ratio of 107 l/min. On average, as much as 76.8 % of the dose was recovered in urine in form of the MAO-catalysed metabolite 4-hydroxyphenylacetic acid (4-HPAA), confirming that oxidative deamination by MAO-A is the quantitatively most relevant metabolic pathway. Systemic exposure of 4-HPAA varied only up to 3-fold, indicating no strong heritable variation in peripheral MAO-A activity. Systolic blood pressure increased by more than 10 mmHg in 71 % of the volunteers and correlated strongly with systemic tyramine concentration. In less than 10 % of participants, individually variable blood pressure peaks by >40 mmHg above baseline were observed at tyramine concentrations of >60 µg/l. Unexpectedly, the functionally relevant polymorphisms in OCT1 and CYP2D6, including the CYP2D6 poor and ultra-rapid metaboliser genotypes, did not significantly affect tyramine pharmacokinetics or pharmacodynamics. Also, the MOA-A genotypes, which had been associated in several earlier studies with neuropsychiatric phenotypes, had no significant effects on tyramine pharmacokinetics or its metabolism to 4-HPAA. Thus, variation in tyramine pharmacokinetics and pharmacodynamics is not explained by obvious genomic variation, and human tyramine metabolism did not indicate the existence of ultra-low or -high MAO-A activity.